Carbon information disclosure quality, greenwashing behavior, and enterprise value - Cao, Qilin; Zhou, Yunhuan; Du, Hongyu; Ren, Mengxi; Zhen, Weili (Frontiers in psychology, 2022)
As global warming becomes increasingly prominent, countries worldwide advocate for a low-carbon economy to cope with the pressure to reduce greenhouse gas emissions. The Chinese government has proposed a “dual carbon” goal of peaking carbon emissions by 2030 and becoming carbon neutral by 2060. The disclosure of carbon information by Chinese enterprises has attracted widespread attention from society. This study selects the constituents of the Social Responsibility Index of China Shanghai Stock Exchange from 2016 to 2020 as samples to empirically analyze the relationship between the level of carbon information disclosure and corporate value, and the moderating effect of greenwashing behavior. Results indicated that the quality of carbon disclosure is positively correlated with the enterprise value. Greenwashing behavior promotes the positive impact of carbon disclosure quality on enterprise value in the short run, but this promoting effect fades in the long run. We further found that the carbon information disclosure of non-heavy-pollution enterprises has a more obvious positive impact on enterprise value than that of heavily polluting enterprises. Additionally, the positive impact of carbon information disclosure on enterprise value is more visible among enterprises in a good legal environment than those in a poor legal environment. This study enriches the relevant literature on carbon information disclosure and enterprise “greenwashing” behavior and has practical significance for promoting China’s low-carbon development in the context of ecological civilization and improving the enthusiasm for the quality of enterprise carbon information disclosure.